P2X7 Purinoceptor Affects Ectopic Calcification of Dystrophic Muscles - Rumney, Robin M. H.; Róg, Justyna; Chira, Natalia; Kao, Alexander P.; Al-Khalidi, Rasha; Górecki, Dariusz C. (Frontiers in Pharmacology, 2022)
Ectopic calcification (EC) of myofibers is a pathological feature of muscle damage in Duchenne muscular dystrophy (DMD). Mineralisation of muscle tissue occurs concomitantly with macrophage infiltration, suggesting a link between ectopic mineral deposition and inflammation. One potential link is the P2X7 purinoceptor, a key trigger of inflammation, which is expressed on macrophages but also up-regulated in dystrophic muscle cells. To investigate the role of P2X7 in dystrophic calcification, we utilised the Dmdmdx-βgeo dystrophin-null mouse model of DMD crossed with a global P2X7 knockout (P2rx7-/-) or with our novel P2X7 knockin-knockout mouse (P2x7KiKo), which expresses P2X7 in macrophages but not muscle cells. Total loss of P2X7 increased EC, indicating that P2X7 overexpression is a protective mechanism against dystrophic mineralisation. Given that muscle-specific P2X7 ablation did not affect dystrophic EC, this underlined the role of P2X7 receptor expression on the inflammatory cells. Serum phosphate reflected dystrophic calcification, with the highest serum phosphate levels found in genotypes with the most ectopic mineral. To further investigate the underlying mechanisms, we measured phosphate release from cells in vitro, and found that dystrophic myoblasts released less phosphate than non-dystrophic cells. Treatment with P2X7 antagonists increased phosphate release from both dystrophic and control myoblasts indicating that muscle cells are a potential source of secreted phosphate while macrophages protect against ectopic mineralisation. Treatment of cells with high phosphate media engendered mineral deposition, which was decreased in the presence of the P2X7 agonist BzATP, particularly in cultures of dystrophic cells, further supporting a protective role for P2X7 against ectopic mineralisation in dystrophic muscle.